Candidate pigmentation genes related to feather color variation in an indigenous chicken breed revealed by whole genome data - Wang, Huie; Wen, Junhui; Li, Haiying; Zhu, Tao; Zhao, Xiurong; Zhang, Jinxin; Zhang, Xinye; Tang, Chi; Qu, Lujiang; Gemingguli, M. (Frontiers in Genetics, 2022)
Chicken plumage color is an inheritable phenotype that was naturally and artificially selected for during domestication. The Baicheng You chicken is an indigenous Chinese chicken breed presenting three main feather colors, lavender, black, and yellow plumages. To explore the genetic mechanisms underlying the pigmentation in Baicheng You chickens, we re-sequenced the whole genome of Baicheng You chicken with the three plumage colors. By analyzing the divergent regions of the genome among the chickens with different feather colors, we identified some candidate genomic regions associated with the feather colors in Baicheng You chickens. We found that EGR1, MLPH, RAB17, SOX5, and GRM5 genes were the potential genes for black, lavender, and yellow feathers. MLPH, GRM5, and SOX5 genes have been found to be related to plumage colors in birds. Our results showed that EGR1 is a most plausible candidate gene for black plumage, RAB17, MLPH, and SOX5 for lavender plumage, and GRM5 for yellow plumage in Baicheng You chicken.